Magnet device to reduce diesel consumption in diesel engine - Ponnusamy, Barath (2011)
The objective of this thesis is to design and fabricate a simple and cheap magnet device to investigate the effect of magnets on fuel consumption and exhaust gas temperature. Permanent magnets are cheap, light in weight, safe and at the same time, it is environmental friendly. The magnet device is easy to attach on the fuel line because it is small. SolidWorks is used to design the magnet device before fabricate this device. The magnet device is then fabricated by using acrylic which not attracted magnetic field so that the magnetic field will be focused on fuel line. The magnets help to disperse the hydrocarbon cluster into smaller particles which will improve the efficiency of combustion. This will maximize the combustion and thus reduce the unburned hydrocarbon in the emission. Then, an experiment is conducted by using a diesel engine without load to determine the fuel consumption and also temperature. A graph is then plotted based on the readings to compare the effects of magnets towards the fuel consumption and temperature